Impact of stand variables on characteristics of avian soundscape in common oak (Quercus robur L.) forests - Atemasov, Andrij; Atemasova, Tetyana (My University, 2019)
One of the problems that may arise when conducting long-term monitoring of bird populations in forest landscapes may be discrepancies between data obtained by different researchers. Using acoustic monitoring may solve this problem. To establish the suitability of the acoustic method for monitoring the state of forest ecosystems, studies were conducted in May and June 2018 on seven plots different from each other by stand age and species composition in a maple-linden-oak forest in northeastern Ukraine. The species composition of birds, the structure and composition of the stand and the values of six acoustic indices were calculated. Differences were found in all acoustic indices at different sites. The smallest values of the indices were noted in the overgrown clear-cut. Four acoustic indices in the May survey and five of the six in the June survey show significant correlations with the species richness of birds. All indices correlate with the values of several stand variables, which characterize the size and species composition of the stand, understorey and field vegetation, the closeness of various vegetation tiers, and with the distance to the edges and the nearest populated areas. The results suggest the possibility of using an acoustic approach to monitoring the bird population and the state of forest ecosystems.
Atemasov A., Atemasovа Т. Impact of stand variables on characteristics of avian soundscape in common oak (Quercus robur L.) forests // Forestry Studies. 2019. Vol.70: Is. 1 DOI: https://doi.org/10.2478/fsmu-2019-0006 https://content.sciendo.com/view/journals/fsmu/70/1/article-p68.xml
Keywords: NATURAL SCIENCES